A Comparison of Sealant Placement Techniques and - Michael J. Kanellis, DDS, MS; Peter C. Damiano, DDS, MPH; Elizabeth T. Momany, PhD (Blackwell Synergy, 2000)
This study compared time required and 12-month retention for two methods of sealant placement: traditional acid-etch technique and air-abrasion technique without acid etch